An ANALYSIS OF STUDENTS’ PROBLEMS IN WRITING AN ESSAY ON THIRD SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM AT STKIP PGRI LUBUKLINGGAU - metria winda (Journal of English Education, Literature and Linguistics, 2019)
Abstract This aims of this research were to find out the students problem in writing an essay and to describe the possible causes of the problems are faced by the students in writing an essay. This research belongs to descriptive qualitative research. The data was gotten from questionnaire and interview from the third semester students of English Education at STKIP-PGRI Lubuklinggau. The data in this research was collected by some steps 1) the researcher gave the questionnaire to students and lecturer 2) the researcher gave the interview to students and lecturer 3) the researcher collected the data to get the data of the students problems in writing an essay. Based on the result from the research in questionnaire and interview of students’ problems in writing an essay, the students had some problems especially in using grammar, vocabulary, cohesion and syntax. And, this result become the next important problems can be analyzed by other researcher.